2018
DOI: 10.18388/abp.2018_2596
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of various soy isoflavone dietary supplements (nutraceuticals) on bacterial growth and human fibroblast viability

Abstract: Flavonoids, polyphenolic compounds present in many food products, affect growth of different bacterial species when tested as purified or synthetic substances. They can also influence gene expression in human cells, like fibroblasts. Here, we asked if soy isoflavone extracts, commonly used in many products sold as anti-menopausal dietary supplements, influence bacterial growth similarly to a synthetic isoflavone, genistein. Four commercially available products were tested in amounts corresponding to genistein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Phytochemical research on PES leaves has revealed the functions of 4 flavonoids and their working mechanisms [7]. Flavonoids are thought to be biologically active natural products present in a variety of fruits, vegetables, grains, and other dietary supplements [8][9][10]; flavonoids have attracted substantial attention because of their antioxidant abilities, chemopreventive properties, and radical scavenging activities, as well as cardiovascular protective, anti-inflammatory, and antiviral effects [11][12][13][14][15][16][17]. There is a growing interest in the analysis and identification of the flavonoid constituents of medicinal plants to identify the structure-activity relationship of flavonoids, as a small difference in the structure of a flavonoid can cause significant changes in its biological activities [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical research on PES leaves has revealed the functions of 4 flavonoids and their working mechanisms [7]. Flavonoids are thought to be biologically active natural products present in a variety of fruits, vegetables, grains, and other dietary supplements [8][9][10]; flavonoids have attracted substantial attention because of their antioxidant abilities, chemopreventive properties, and radical scavenging activities, as well as cardiovascular protective, anti-inflammatory, and antiviral effects [11][12][13][14][15][16][17]. There is a growing interest in the analysis and identification of the flavonoid constituents of medicinal plants to identify the structure-activity relationship of flavonoids, as a small difference in the structure of a flavonoid can cause significant changes in its biological activities [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Genistein is another flavonoid with a therapeutic potential in AD [ 43 ]. Like all flavonoids, genistein has antioxidant and anti-inflammatory properties and stimulates autophagy [ 44 ].…”
Section: Overview Of the Use Of Flavonoids In Neurodegenerative Disor...mentioning
confidence: 99%
“…Isoflavones are a subclass of flavonoids and the most common phytoestrogens. 16 , 17 Biological activities of isoflavones present in dietary supplements have been widely studied, 18 , 19 , 20 for example, isoflavone impact on the health of postmenopausal women. 21 , 22 Isoflavones prevent bone resorption, 23 , 24 , 25 moreover they increase the efficacy and prevent the adverse effects of cancer chemotherapy and radiation therapy.…”
Section: Introductionmentioning
confidence: 99%